An enhanced key generation and key security of beaufort cipher expansion technique using pseudo-random number, key encryption, and alphabet extension applied in text data - Bacaris, Andrea B.; Dejacto, Ma. Genina S. 4 0 16; 5 (2023)
u
Undergraduate Thesis: (Bachelor of Science in Computer Science) Pamantasan ng Lungsod ng Maynila, 2023.
Keywords: 2 -- 0; 6; 20; 20; 2